Milkfish nugget formulation with carrot and sweet corn modification towards nutritional status enhancement for underweight - Hamzah, Diza Fathamira; Putri, Elisa (AcTion: Aceh Nutrition Journal, 2021)
Milkfish nugget is one of nutritionally dense processed with a practical presentation and generally liked by children. To enrich the nutritional content, the manufacture of nuggets is modified with the addition of vegetables including carrots and sweet corn. The modification of milkfish nuggets with carrots and sweet corn can be used as additional food for underweight toddlers This study aims to determine the effect of milkfish nuggets formulation with carrots and sweet corn modification. This research was a quasi-experiment with one group pre and post-test design. The sample was 37 with the total sampling method. The data was collected by observing the enhancement of toddlersâ€™ nutritional status during 10 days. Data were analyzed by using a paired T-test with aÂ  95% confidence interval. The results showed the bodyweight average increase after giving milkfish nuggets was 800 grams with an enhancement in nutritional from the average Z-score value of -1,95 through the bodyweight for age indicator. The milkfish nuggets formulation had a significant effect in enhancing the nutritional status of underweight toddlers (p-value 0,002). It is necessary to improve the quality of health programs especially regarding food intake for underweight toddlers to achieve the quality of the human development index.